The de novo DNA methyltransferase 3B is a novel epigenetic regulator of MYC in multiple myeloma, representing a promising therapeutic target to counter relapse - Catharina Muylaert; Lien Ann Van Hemelrijck; Arne Van der Vreken; Robbe Heestermans; Hatice Satilmis; Emma Verheye; Elina Alaterre; Catharina Olsen; Nathan De Beule; Kim De Veirman; Eline Menu; Karin Vanderkerken; et al. (Journal of Experimental & Clinical Cancer Research)
Abstract Background The plasma cell malignancy multiple myeloma (MM) remains incurable due to the inevitable development of drug resistance (DR). Epigenetic modifiers are frequently mutated or deregulated in MM patients, contributing to MM progression and relapse. Overexpression of the de novo DNA methyltransferase 3B (DNMT3B) in MM has been reported, correlating with poor prognosis. However, its exact role in MM cell biology and relapse remains elusive. Methods To evaluate the basal expression and prognostic value of DNMT3B mRNA in terms of overall survival the publicly available gene expression profiling datasets GSE2658, GSE9782, GSE4581, E-MTAB-372, E-TABM-1088 and E-TABM-937 were used. Both the DNMT3B selective inhibitor Nanaomycin A and genetic knockdown using a doxycycline inducible shRNA against DNMT3B were used to target DNMT3B. Viability and apoptosis were assessed using respectively a CellTiter-Glo assay and AnnexinV/7AAD stainings. Cell proliferation was measured by BrdU incorporation and cell cycle analysis, while the clonogenic capacity was evaluated by a colony formation assay. Finally, RNA-seq was performed upon genetic knockdown. Results Here, we show that DNMT3B is significantly increased in the relapsed setting and high DNMT3B levels are strongly correlating with disease progression and high-risk disease, irrespective of the treatment. Targeting DNMT3B using either genetic inhibition or the selective inhibitor Nanaomycin A strongly impaired MM cell growth, survival and clonogenicity. Moreover, Nanaomycin A reduced viability of primary MM cells from newly diagnosed and relapsed patients. Mechanistic studies revealed that DNMT3B inhibition mainly affects cell cycle and stemness-related transcriptional programs. Notably, DNMT3B depletion affected the stability of the master cell cycle regulator MYC, thereby reducing c-MYC levels and cell viability both in parental and c-MYC overexpressing cells. Finally, Nanaomycin A (re)sensitized MM cells to bortezomib, melphalan and anti-CD38 monoclonal antibodies (daratumumab, isatuximab). Conclusion Collectively, our findings uncover DNMT3B as a targetable vulnerability in high-risk patients with high DNMT3B/MYC levels.